The RNA helicase DDX6 controls early mouse embryogenesis by repressing aberrant inhibition of BMP signaling through miRNA-mediated gene silencing - Jessica Kim; Masafumi Muraoka; Hajime Okada; Atsushi Toyoda; Rieko Ajima; Yumiko Saga (PLoS Genetics, 2022)
The evolutionarily conserved RNA helicase DDX6 is a central player in post-transcriptional regulation, but its role during embryogenesis remains elusive. We here show that DDX6 enables proper cell lineage specification from pluripotent cells by analyzing Ddx6 knockout (KO) mouse embryos and employing an in vitro epiblast-like cell (EpiLC) induction system. Our study unveils that DDX6 is an important BMP signaling regulator. Deletion of Ddx6 causes the aberrant upregulation of the negative regulators of BMP signaling, which is accompanied by enhanced expression of Nodal and related genes. Ddx6 KO pluripotent cells acquire higher pluripotency with a strong inclination toward neural lineage commitment. During gastrulation, abnormally expanded Nodal and Eomes expression in the primitive streak likely promotes endoderm cell fate specification while inhibiting mesoderm differentiation. We also genetically dissected major DDX6 pathways by generating Dgcr8, Dcp2, and Eif4enif1 KO models in addition to Ddx6 KO. We found that the miRNA pathway mutant Dgcr8 KO phenocopies Ddx6 KO, indicating that DDX6 mostly works along with the miRNA pathway during early development, whereas its P-body-related functions are dispensable. Therefore, we conclude that DDX6 prevents aberrant upregulation of BMP signaling inhibitors by participating in miRNA-mediated gene silencing processes. Overall, this study delineates how DDX6 affects the development of the three primary germ layers during early mouse embryogenesis and the underlying mechanism of DDX6 function. Author summary Gene expression occurs through two steps: transcription (DNA to RNA) and translation (RNA to protein). Cells have highly sophisticated regulatory processes working on various levels for accurate gene expression. Post-transcriptional regulation, which includes all RNA-related controls, is crucial because it enables fine-tuning and rapid alteration of gene expression. RNA-binding proteins and non-coding RNAs are the two main players in post-transcriptional regulation. DDX6, the subject of our study, is an RNA-binding protein, more specifically an RNA helicase, which can unwind or rearrange RNA secondary structures. Its diverse molecular and cellular functions have been reported, but its embryogenic role is unknown. Here, we describe DDX6 function during early mouse embryogenesis and the underlying mechanism using genetic methodology. DDX6 enables proper cell lineage specification of pluripotent stem cells by mainly regulating BMP signaling through miRNA-mediated gene silencing. As DDX6-mediated RNA regulation affects signaling pathways, the loss of DDX6 has a wide impact on developmental processes from pluripotency to embryo patterning. In addition to showing the developmental role of DDX6, we succeeded in the modular segregation of its various RNA-regulatory pathways. Considering the presence of DDX6 in diverse contexts, such as cancer, virus infection, and stem cells, this new knowledge forms a foundation for DDX6 being a good therapeutic target.